Answer:
2.Solve for the first variable in one of the equations, then substitute the result into the other equation.
Point Form:
(
3
,
5
)
Equation Form:
x
=
3
,
y
=
5
3.Solve for the first variable in one of the equations, then substitute the result into the other equation.
Point Form:
(
2
,
8
)
4.Solve for the first variable in one of the equations, then substitute the result into the other equation.
Point Form:
(
2
,
−
3
)
Step-by-step explanation:
Answer:
12x + 2
Step-by-step explanation:
Let the number be represented by x.
Then five times the number = 5*x
Seven times the number = 7*x
Sum of 5 times the number minus -2 =
= ![\[5x +2\]](https://tex.z-dn.net/?f=%5C%5B5x%20%2B2%5C%5D)
Adding seven times the number to this expression yields, ![\[5x+2+7x\]](https://tex.z-dn.net/?f=%5C%5B5x%2B2%2B7x%5C%5D)
![\[= (5+7)x+2\]](https://tex.z-dn.net/?f=%5C%5B%3D%20%285%2B7%29x%2B2%5C%5D)
![\[= 12x+2\]](https://tex.z-dn.net/?f=%5C%5B%3D%2012x%2B2%5C%5D)
So the simplified expression corresponds to 12x + 2.
Answer:
-1
Step-by-step explanation:
Ghana is a great place to work for and it is the most versatile and affordable way to do business with you in the future of the following statements is of a hole in your heart to be added
Answer:
138
Step-by-step explanation:
as 92÷4 = 23 and 23x6 = 148
Solution:
1) Simplify \frac{1}{6}x to \frac{x}{6}
y=\frac{x}{6}-2
2) Add 2 to both sides
y+2=\frac{x}{6}
3) Multiply both sides by 6
(y+2)\times 6=x
4) Regroup terms
6(y+2)=x
5) Switch sides
x=6(y+2)
Done!